Catolicismos alternativos: das dissidências com a Igreja Católica Romana às novas fundações - o caso da Igreja Católica Apostólica Carismática (ICAC) - Silva, Marcos Aurélio da (2019)
This dissertation is the result of the study of the dissent and different inventions of Catholic churches in Brazil that, despite the similarities in form and content, do not belong to the Roman Apostolic Catholic Church. It is considered pertinent to carry out this research due to the scarce academic bibliography about the different Catholic churches that spread throughout Brazil, without, however, knowing what their origins are. In this sense, this work aims, besides knowing the identity of a specific Catholic Church, the Charismatic Apostolic Catholic Church, to help arouse interest in the theme. Specifically, it aims to capture the identity of the Charismatic Apostolic Catholic Church (ICAC), which was established in 2013, in the city of Taubaté-SP, about which very little was known until then. Methodologically, bibliographical and documentary research and participative observation of the masses were carried out, mainly in the Church of Taubaté-SP and, eventually, in the Churches of Rio Claro-SP and in São Paulo, in the church of Bairro do Belém. Conclude that their origin is among the various churches that formed from successive dissent of the Brazilian Apostolic Catholic Church (ICAB) although, as time distances them from that, it becomes inappropriate to infer any direct relationship between these new foundations and the ICAB. The difficulties in factually knowing the origin of the ICAC may be justified by the absence of a “founding myth” or even a (relevant) fact that would have given rise to the “new” church. In this sense, as a result, one of the recurring discourses at the ICAC Masses can be understood: “No matter where you come from and what your condition is, the priest prays, and the miracle happens in your life and you repay God with the holy tithe.". Following the same reasoning, it does not seem wrong to infer the church's rhetoric: no matter where the church comes from, it does the miracles it can work in its life